The Philosophical Power of Civic Education 21st Century in Indonesia - Gunawan Santoso (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Civic education is a subject and course that has a great responsibility in building the character of democracy and the tolerance of students, because civic education is a moral education and must be administered at every level of education from elementary to college. Civic education is subjects and courses of moral education that should be able to minimize even the conflict among learners. This research uses the method of literature analysis with grounded theory is a qualitative research method that uses a number of systematic procedures to develop a theory compiled inductive. Research grounded theory, this research inductive research techniques, emphasizes observation and develops a base of "intuitive" relationship practices between variables. Then the philosophical practice of Civic Education in Indonesia is a curricular program to form human individuals who are moral/character statesman, noble morality, intelligent, believer and fear Allah according to the content of the and Pancasila, with the way to give an intake of knowledge about the meaning and meaning of the moral value of Pancasila, adherence to the constitution Nri 1945, with a democracy Berbhinneka Tunggal Ika, which is tied strongly in a container of the unitary Republic of Indonesia, through the agreement of Youth Oath and a commitment that remains one in the red white flag, by producing human output of science, capable, creative, and independent by the deeds of the Soul statesman, heroism, nationalism, Fruitful happy ending by giving a good benefit to yourself, family, school, Nation and country of Indonesia